Waste cooking oil transesterification: influence of impeller type, speed and bottom clearance on fame yield - Adeyemi, Nabeel A.; Mohiuddin, A. K. M.; Jameel, Ahmed Tariq (2011)
This work is presented as part of a study to model transesterification of waste cooking oil (WCO). At an alcohol:oil mole ratio of 6:1 and catalyst 2% (oil wt) the Taguchi method was used to design and analyze the experimental result for WCO transesterification in a 2 Liter stirred reactor using Rushton and Elephant ear impellers. The orthogonal array (OA) L9 design in Taguchi method was used to obtain the optimum Fatty acid methyl ester (FAME) yield. An optimum condition of 70ºC, 650 rpm impeller speed and impeller bottom distance of 30 mm for Rushton Impeller and 70ºC, 700 rpm impeller speed and impeller bottom distance of 25 mm using an elephant ear impeller resulted in FAME yield of 89-94%. From the Signal noise (SN) ratio of the mean effect (yield), the impeller bottom distance and speed were observed to have the most significant effect on yield using the Rushton and elephant ear impeller respectively. Peak yield time between 5-30 minutes was observed using the dynamic Taguchi method. This result shows the significance of internal physical configuration in stirrer reactor, which subsequently affected FAME yield and peak yield time.